Solve the equation −x2−3x=5−3x

and re-express the answer as a complex number with the imaginary unit.
explain how you get the answer

1 answer

To solve the equation -x^2 - 3x = 5 - 3x, we can start by subtracting 5 and adding 3x to both sides of the equation:

-x^2 - 3x - 3x = 5 - 3x - 3x
-x^2 - 3x - 3x + 6x = 5 - 6x
-x^2 = 5 - 6x

Next, we can move the -6x term to the left side by adding 6x to both sides:

-x^2 + 6x = 5

Now, we can rearrange the equation to have the quadratic term positive:

x^2 - 6x = -5

In this form, we can use the quadratic formula to solve for x. The quadratic formula states that for an equation of the form ax^2 + bx + c = 0, the solutions for x are given by:

x = (-b ± √(b^2 - 4ac)) / (2a)

In our case, a = 1, b = -6, and c = -5. Plugging these values into the quadratic formula:

x = (-(-6) ± √((-6)^2 - 4(1)(-5))) / (2(1))
x = (6 ± √(36 + 20)) / 2
x = (6 ± √56) / 2

Simplifying further:

x = (6 ± 2√14) / 2
x = 3 ± √14

So the solutions to the equation -x^2 - 3x = 5 - 3x are x = 3 + √14 and x = 3 - √14.

Now, to re-express these solutions as complex numbers with the imaginary unit, we can rewrite them as:

x = 3 + √14 + 0i
x = 3 - √14 + 0i

There is no imaginary part because the solutions do not involve the imaginary unit, i.
Similar Questions
  1. Complex Numbers Unit Test5 of 255 of 25 Items Question Solve the equation −x2−3x=5−3x and re-express the answer as a
    1. answers icon 1 answer
  2. only one anwserComplex Numbers Unit Test 5 of 255 of 25 Items Question Solve the equation −x2−3x=5−3x and re-express the
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions